A rare case report of hemolysis in a newborn: hereditary elliptocytosis - Jiang, Shouliang; Lu, Ruifeng; Tang, Jun (Frontiers in Pediatrics, 2024)
Introduction: Hereditary Elliptocytosis (HE) comprises clinically and genetically heterogeneous red cell membranopathies resulting from defects in the horizontal linkage between red blood cell (RBC) membrane and cytoskeletal proteins, which affect mechanical stability and deformability, thereby reducing RBC lifespan. The principal defect in HE is due to dysfunction or deficiency of RBC cytoskeletal proteins.Case Description: This study reported a case of severe hemolysis occurring within one day after birth in a term newborn. High-throughput sequencing was used to characterize the pathogenic gene variation in this child and to study the correlation between the identified variation and its corresponding phenotypic characteristics.HE is caused by monoallelic mutations, which justify the phenotypic heterogeneity observed in patients. Furthermore, molecular analysis using high-throughput sequencing enables diagnosis in disorders with highly variable heterogeneity. HE can also present with severe hemolysis during the neonatal period.